2016
DOI: 10.1038/ncomms10330
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress drives proteinuria-induced kidney lesions via Lipocalin 2

Abstract: In chronic kidney disease (CKD), proteinuria results in severe tubulointerstitial lesions, which ultimately lead to end-stage renal disease. Here we identify 4-phenylbutyric acid (PBA), a chemical chaperone already used in humans, as a novel therapeutic strategy capable to counteract the toxic effect of proteinuria. Mechanistically, we show that albumin induces tubular unfolded protein response via cytosolic calcium rise, which leads to tubular apoptosis by Lipocalin 2 (LCN2) modulation through ATF4. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
96
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 53 publications
(69 reference statements)
1
96
0
4
Order By: Relevance
“…Tear lipocalin transports and/or sequesters phospholipids within the tear film to enable proper lubrication of the eye (Glasgow et al 1995;Gouveia and Tiffany 2005). Lipocalin2 (Lcn2, also known as 24p3 or neutrophil gelatinase associated lipocalin) sequesters iron-containing siderophores to protect against bacterial infections (Flo et al 2004), and can influence signaling by hepatocyte growth factor during kidney tube development (Wu and Han 1994;Gwira et al 2005;El Karoui et al 2016). The lipocalin Swim (secreted interacting Wnt molecule) facilitates transport of lipid-modified Wnt ligands (Mulligan et al 2012), and the plasma lipocalin apolipoprotein M (ApoM) facilitates transport of the signaling lipid sphingosine-1-phosphate (S1P) (Christoffersen et al 2011).…”
mentioning
confidence: 99%
“…Tear lipocalin transports and/or sequesters phospholipids within the tear film to enable proper lubrication of the eye (Glasgow et al 1995;Gouveia and Tiffany 2005). Lipocalin2 (Lcn2, also known as 24p3 or neutrophil gelatinase associated lipocalin) sequesters iron-containing siderophores to protect against bacterial infections (Flo et al 2004), and can influence signaling by hepatocyte growth factor during kidney tube development (Wu and Han 1994;Gwira et al 2005;El Karoui et al 2016). The lipocalin Swim (secreted interacting Wnt molecule) facilitates transport of lipid-modified Wnt ligands (Mulligan et al 2012), and the plasma lipocalin apolipoprotein M (ApoM) facilitates transport of the signaling lipid sphingosine-1-phosphate (S1P) (Christoffersen et al 2011).…”
mentioning
confidence: 99%
“…9 In this case, the PERK arm of the UPR may also trigger activation of ATF4, a transcription factor that increases the transcription of pro-apoptoticgenes such as CHOP (CCAAT-enhancer-binding protein homologous protein) and decreases antiapoptotic genes such as B-cell lymphoma 2 (Bcl-2). [1][2][3]8 Furthermore, the IRE1α arm may also activate Caspase 12 (rodents)/Caspase 4 (humans) and c-Jun N-terminalkinase (JNK) phosphorylation, leading to initiation of pro-apoptotic pathways. 3 Thus, the UPR is a double-edged sword acting as either a cell-protective machinery during mild ER stress or a cell-destructive terminator during severe or long-term ER stress.…”
Section: -8mentioning
confidence: 99%
“…Interestingly, accumulating evidence has shown the association of ER stress and dysregulated UPR with the pathogenesis of CDK. [1][2][3][4][5][6][7][8] Several lines of evidence from clinical and experimental studies have revealed that the accumulation of misfolded proteins of the slit diaphragm elicits ER stress-associated renal injury and proteinuria. 1,2 It has been demonstrated that various pathogenic factors, such as proteinuria, hyperglycemia, and uremic toxins, induce UPR-mediated cell apoptosis, compromise the repair capacity of tubular epithelial cells, and accelerate the progression of CKD.…”
Section: -8mentioning
confidence: 99%
See 2 more Smart Citations